Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Kemampuan Pemecahan Masalah dan Hasil Belajar Kognitif Siswa Biologi Kelas XI SMA - Riskayanti, Dwi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Based on the results of preliminary observations at SMA Negeri 1 Jereweh, West Sumbawa Regency, it shows that students are less involved in the learning process and students tend to be passive. One of the factors that causes students to be less involved in learning is because the learning model and learning approach applied by the teacher are less varied. Therefore, research has been conducted on the effect of the Guided Inquiry learning model on problem-solving abilities and cognitive learning outcomes of Class XI Biology students at SMA Negeri 1 Jereweh. The purpose of this study was to examine whether there was an effect of the Guided Inquiry learning model on problem solving abilities and cognitive learning outcomes of class XI students of SMA Negeri 1 Jereweh. The type of research used in this research is Quasi Experiment. The research design in this research was pre-test and post-test, and the research samples were 19 students from class XI IPA 1 as the experimental class, and 18 students from class XI IPA 2 as the control class. Data collection uses observation sheets to determine students' problem solving abilities and test sheets to determine students' cognitive learning outcomes. Based on the results of data analysis, the average value of the control class for problem solving ability was 82.5% in the high category, and the average value of the experimental class for problem solving ability was 90.62% in the very high category. The average value for the cognitive learning outcomes of the control class was 77.2, while the average value for the experimental class was 85.7. Testing the hypothesis using t-test analysis (t-test) at a significant level of 5%, obtained a tcount of 6.248 > ttable value of 1.684, so it can be concluded that there is an influence of the Guided Inquiry learning model on cognitive learning outcomes of class XI students of SMA Negeri 1 Jereweh.